Spins and shapes of 11 near-Earth asteroids observed within the NEOROCKS project - Fatka, Petr; Pravec, P.; Scheirich, P.; Kušnirák, P.; Hornoch, K.; Kučáková, H.; Ergashev, K. E.; Souza de Joode, Marco; Burkhonov, O. A.; Ehgamberdiev, S. A.; Galád, A.; Világi, J.; et al. (Astronomy and astrophysics, 2025)
Context. The discovery rate of near-Earth asteroids (NEAs) has steadily increased over the past three decades, yet the physical characterization of these objects has not kept pace. Aims. In an effort to help address this gap, we combined targeted photometric observations, archival data, and sparse photometric data from the Asteroid Terrestrial-impact Last Alert System (ATLAS) survey to extract as much information as possible about NEAs’ rotation rates, spin-axis orientations, and shapes. Methods. We selected 17 NEAs with a potential for shape reconstruction and applied the light curve inversion method to derive their sidereal rotation periods, spin-axis directions, and convex shape models. Results. We successfully determined unique spin and shape models for seven NEAs: (5189) 1990 UQ, (6569) Ondaatje, (7025) 1993 QA, (8566) 1996 EN, (86450) 2000 CK33, the Hayabusa2# flyby target (98943) 2001 CC21, and (512245) 2016 AU8. For an additional four asteroids – (66251) 1999GJ2, (137199) 1999KX4, (276786) 2004 KD1, and (495615) 2015 PQ291 – we constrained their sidereal periods, spin-axis orientations, and in some cases, their shapes. Conclusions. This study highlights the importance of integrating new photometric data with archival dense light curves and sparse observations to improve the physical characterization of NEAs, even when working with suboptimal datasets. We constructed 11 NEA models, contributing to the limited set of a few dozen models derived from space missions, radar observations, and light curve inversions.
Online verfügbar: 14. März 2025
Gesehen am 10.11.2025